2011
DOI: 10.1080/01490451.2010.507646
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Uranyl Speciation and Iron Oxides on Uranium Biogeochemical Redox Reactions

Abstract: Uranium is a pollutant of concern to both human and ecosystem health. Uranium's redox state often dictates its partitioning between the aqueous-and solid-phases, and thus controls its dissolved concentration and, coupled with groundwater flow, its migration within the environment. In anaerobic environments, the more oxidized and mobile form of uranium (UO 2 2+ and associated species) may be reduced, directly or indirectly, by microorganisms to U(IV) with subsequent precipitation of UO 2 . However, various fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 45 publications
6
41
0
Order By: Relevance
“…These observations revealed that, in carbonatebearing waters, neutral to slightly acidic pH values (∼5) and limited dissolved Ca were optimal for uranium sorption. Steward et al [77,78] further investigated the impact of U(VI) speciation on the extent and rate of biological reduction, with specific emphasis on the impact of dissolved Ca and the FHOs (ferrihydrite, goethite and hematite) on reduction. The amount of U removed from solution during 100 h of incubation with a microbial S. putrefaciens was 77% with no Ca or ferrihydrite present, but only 24% (with ferrihydrite) and 14% (no ferrihydrite) were removed from 0.8 mM Ca systems.…”
Section: Effects Of Ca and Carbonate Species Or P Comentioning
confidence: 98%
“…These observations revealed that, in carbonatebearing waters, neutral to slightly acidic pH values (∼5) and limited dissolved Ca were optimal for uranium sorption. Steward et al [77,78] further investigated the impact of U(VI) speciation on the extent and rate of biological reduction, with specific emphasis on the impact of dissolved Ca and the FHOs (ferrihydrite, goethite and hematite) on reduction. The amount of U removed from solution during 100 h of incubation with a microbial S. putrefaciens was 77% with no Ca or ferrihydrite present, but only 24% (with ferrihydrite) and 14% (no ferrihydrite) were removed from 0.8 mM Ca systems.…”
Section: Effects Of Ca and Carbonate Species Or P Comentioning
confidence: 98%
“…This process can result in the formation of various Fe-containing secondary phases, such as green rust, goethite, magnetite, siderite, vivianite, and so on (Nealson and Saffarini, 1994;Fredrickson et al, 1998;Dong et al, 2000;Kukkadapu et al, 2001;Parma et al, 2001;Zachara et al, 2002;Hansel et al, 2003). Besides, microbial redox reactions of iron in soils and sediments can significantly affect the geochemistry of other elements or minerals, e.g., decomposition of organic matters (Lovley and Phillips, 1986;Roden et al, 2010), decomposition and dissolution of various minerals (Dong et al, 2003a,b;Seabaugh et al, 2006), and the mobilization or immobilization of many anions and cations including radionuclides and toxic metals (Lack et al, 2002;Stewart et al, 2011;Masue-Slowey et al, 2011;Lu and Wang, 2012). In the last decades, the DIRB reduction of Fe(III) oxides/oxyhydroxides, such as ferrihydrite (Hansel et al, 2003), goethite (Kukkadapu et al, 2001), amorphous hydrous ferric oxide (Fredrickson et al, 1998), and magnetite (Dong et al, 2000) as well as clay minerals containing Fe(III) (Kostka et al, 1999a,b;Dong et al, 2003a), have been well investigated.…”
Section: Introductionmentioning
confidence: 96%
“…Decreased bioreduction rates in the presence of dissolved inorganic carbon (DIC) and Ca 2+ are attributed to the formation of stable uranyl carbonate and ternary Ca uranyl carbonate complexes which are less thermodynamically favorable for reduction and may be inaccessible to bacteria due to steric hindrance or poor affinity for adsorption to the cell membrane (Brooks et al, 2003;Sheng and Fein, 2014;Sheng et al, 2011;Stewart et al, 2011;Ulrich et al, 2011). Similarly, low molecular weight organic acids (Francis and Dodge, 2008;Haas and Northup, 2004;Sheng et al, 2011;Suzuki et al, 2010) and soil humics (Burgos et al, 2007;Gu et al, 2005) may prevent microbial reductive precipitation of uranium by decreasing the bioavailability of U(VI) (e.g., imparting steric hindrance) and/or increasing the solubility of U(IV).…”
Section: Introductionmentioning
confidence: 99%